THE RELATIONSHIP BETWEEN TRADING VOLUME AND STOCK PRICE VOLATILITY IN THE INDONESIAN CAPITAL MARKET - Hafifa Delly (GLOBAL RESEARCH IN ECONOMICS AND ADVANCE THEORY (GREAT), 2024)
This study investigates the relationship between trading volume and stock price volatility in the Indonesian capital market, an emerging market characterized by rapid investor growth and heightened sensitivity to global shocks. Using daily data from 100 companies listed on the Indonesia Stock Exchange (IDX) between 2018 and 2023, including LQ45 constituents, the analysis employs regression and correlation models, controlling for firm size, sector, interest rates, and inflation. Volatility is measured by the standard deviation of daily returns, while trading volume is captured in absolute and average daily terms. The results reveal a strong positive correlation (r = 0.65) between trading activity and volatility, confirming that heightened trading often amplifies price fluctuations. Regression analysis shows that a 1% increase in trading volume leads to a 0.5% rise in volatility (p < 0.01). Sectoral heterogeneity is evident, with technology stocks showing the strongest sensitivity (r = 0.72) and consumer goods displaying moderate responses. The findings underscore that while trading volume is a critical driver of volatility, external shocks and investor sentiment also play important roles. This research contributes to the literature by providing large-scale empirical evidence from Indonesia and offers practical implications for investors and regulators in managing risk and ensuring market stability.